(untitled) (Contemporary Journal of Social Science Review, 2025)
This research explores Pakistan’s Blue Economy, focusing on the sustainable use of ocean resources to drive economic growth and preserve marine ecosystems. Despite its rich marine resources, Pakistan faces challenges like overfishing, pollution, and weak governance, hindering the development of key sectors such as fisheries, offshore energy, and eco-tourism. The study uses a mixed-methods approach, combining qualitative techniques (semi-structured interviews, focus groups) with quantitative methods (structured surveys and secondary data analysis) to gather insights from key stakeholders, coastal communities, and existing reports. Findings show that while the Blue Economy has significant potential, barriers like pollution, governance issues, and lack of infrastructure remain. There is strong support for sustainable practices, but local communities need more support to adopt these policies. In conclusion, the Blue Economy could greatly contribute to Pakistan’s economy and climate resilience, but requires a coordinated approach involving the government, local communities, and the private sector. Key recommendations include creating a unified Blue Economy policy, improving enforcement, investing in eco-tourism, and building local capacity for sustainable practices.